Osteoblastic protein tyrosine phosphatases inhibition and connexin 43 phosphorylation by alendronate - Lezcano, Virginia Alicia (2014)
Bisphosphonates (BPs), potent inhibitors of bone resorption which inhibit osteoclasts, have also been shown to act on osteocytes and osteoblasts preventing apoptosis via connexin (Cx) 43 hemichannels and activating the extracellular signal regulated kinases ERKs. We previously demonstrated the presence of a saturable, specific and high affinity binding site for alendronate (ALN) in osteoblastic cells which express Cx43. However, cells lacking Cx43 also bound BPs. Herein we show that bound [3H]-alendronate is displaced by phosphatase substrates. Moreover, similar to Na3VO4, ALN inhibited the activity of transmembrane and cytoplasmic PTPs, pointing out the catalytic domain of phosphatases as a putative BP target. In addition, anti-phospho-tyrosine immunoblot analysis revealed that ALN stimulates tyrosine phosphorylation of several proteins of whole cell lysates, among which the major targets of the BP could be immunochemically identified as Cx43. Additionally, the transmembrane receptor-like PTPs, RPTPµ and RPTPα, as well as the cytoplasmic PTP1B, are highly expressed in ROS 17/2.8 cells. Furthermore, we evidenced that Cx43 interacts with RPTPµ in ROS 17/2.8 and ALN decreases their association. These results support the hypothesis that BPs bind and inhibit PTPs associated to Cx43 or not, which would lead to the activation of signaling pathways in osteoblasts.